Serial circulating tumor DNA monitoring of CDK4/6 inhibitors response in metastatic breast cancer. Issue 5 (9th March 2022) - Chin, Yoon Ming; Shibayama, Tomoko; Chan, Hiu Ting; Otaki, Masumi; Hara, Fumikata; Kobayashi, Takayuki; Kobayashi, Kokoro; Hosonaga, Mari; Fukada, Ippei; Inagaki, Lina; Ono, Makiko; Ito, Yoshinori; et al.
Abstract: Cyclin‐dependent kinase 4/6 inhibitors (CDK4/6i) significantly improve progression‐free survival and have become the standard therapy for estrogen receptor‐positive/human epidermal growth factor receptor 2‐negative metastatic breast cancer patients. Treatment surveillance by radiological imaging has some limitations in detection and repeated biopsy genomic profiling is not clinically feasible. Serial circulating tumor DNA (ctDNA) analysis may provide insights into treatment response. Here we performed serial ctDNA analysis ( n  = 178) on 33 patients. Serial ctDNA analysis identified disease progression with sensitivity of 75% and specificity of 92%. In eight of 12 patients (61%) responding to CDK4/6i who eventually developed progressive disease, serial sampling every 3 or 6 months captured the initial rise of ctDNA with an average lead time of 3 months. In three of eight patients that did not respond to CDK4/6i (progressive disease at first radiological assessment, 3 months), biweekly sequencing within the first cycle of CDK4/6i treatment (1 month) detected sustained ctDNA levels (≥0.2% variant allele frequency), with lead time of 2 months. Serial ctDNA analysis tracked RECIST response, including clinically challenging scenarios (bone metastases or small‐sized target lesions), as well as detecting acquired genetic alterations linked to CDK4/6i resistance in the G1 to S transition phase. Circulating tumor DNA analysis was more sensitive than carcinoembryonic antigen or cancer antigen 15‐3 serum tumor markers at monitoring tumor response to CDK4/6i treatment. Our findings indicated the possible clinical utility of serial ctDNA analysis for earlier progressive disease detection and real‐time monitoring of CDK4/6i response. Abstract : Cyclin‐dependent kinase 4/6 inhibitors (CDK4/6i) significantly improve progression‐free survival and have become the standard therapy for ER+/HER2− metastatic breast cancer patients. Treatment surveillance by radiological imaging has some limitations in detection and repeated biopsy genomic profiling is not clinically feasible. Our findings showed the possible clinical utility of serial circulating tumor DNA analysis for earlier progressive disease detection and real‐time monitoring of CDK4/6i response.